AB0189 3d skin organoid mimicking systemic sclerosis generated by patient-derived induced pluripotent stem cells: 'disease in a dish' and development of animal model. (12th June 2018) - Kim, J.-W.; Kim, Y.; Kim, J.; Park, M.-J.; Kwon, E.; Lee, J.; Kwok, S.-K.; Ju, J.H.; Park, S.-H.
Abstract : Background: Systemic sclerosis (SSc) is a rare autoimmune disease characterised by vasculopathy and fibrosis of various organs including skin. Although SSc has high morbidity and mortality, evidences for disease modifying treatment are still lacking due to difficulties in performing clinical trials. Patient-specific induced pluripotent stem cells (iPSCs), which can differentiate into various cell types, are used in 3D organoid formation. Objectives: We generated 3D skin organoid model from SSc-derived iPSCs by differentiating them into keratinocytes and fibroblasts. SSc-mimicking 3D skin organoid can be used in studies for disease modelling and drug screening. Methods: Peripheral blood mononuclear cells (PBMCs) from patients with SSc were reprogrammed to iPSCs. SSc-derived iPSCs differentiated into keratinocytes and fibroblasts in vitro . Expression of markers for iPSCs, keratinocytes, and fibroblasts were determined by reverse transcription polymerase chain reaction (RT-PCR) analysis and immunofluorescence assay (IFA). 3D skin organoid using iPSC-derived differentiation cell line was generated by 3D culture system. Histologic analysis was performed on 3D skin organoid. SSc-derived 3D skin organoid was applied to SCID skin defect mice. Histologic analysis was also performed on SCID skin graft model. Results: SSc-derived iPSCs formed colonies that resemble embryonic stem cells. Alkaline phosphatase staining showed undifferentiated state of iPSCs. Expression of iPSC markers was increased on SSc-iPSCs. Differentiated keratinocytes and fibroblasts from iPSCs highly expressed their markers for keratinocytes and fibroblasts, respectively. Dermis of SSc-derived 3D skin organoid was thicker and denser than that derived from healthy control. Epidermis and dermis of SCID skin graft model were thickened in those derived from SSc compared to those derived from healthy control. Conclusions: Patient-derived 3D skin organoid and animal model well represented the characteristics of SSc. These models can serve as useful research tools to understand the disease and screen new drugs for SSc. Disclosure of Interest: None declared